GENITO-URINARY FISTULA: A MAJOR MORBIDITY IN DEVELOPING COUNTRIES - Sachdev, Pushpa Srichand; Hassan, Nabila; Abbasi, Razia Mustafa; Das, Chandra Madhu (Journal of Ayub Medical College Abbottabad, 2009)
Background: Uro-genital fistulas, majority of which are vesico-vaginal fistulas (VVF), are a great challenge for women in developing countries. It is commonly caused by prolong obstructed labour and is one of the worst complications of child birth and poor obstetric care. The objective of this descriptive study was to review the cases of genitourinary fistulae so as to understand the magnitude of the problem and its aetiology and to share our experience of surgical repair with other specialists in this field. The study was conducted at Gynaecological Unit-II, Liaquat University Hospital Hyderabad, Pakistan from June 1996 to December 2007. Methods: The case records of all patients admitted and managed during study period were reviewed. The information regarding characteristics, risk factors and surgical management was collected. The data was analysed by SPSS and mean, range, standard deviation and percentage were calculated. Results: During the study period, 278 patients with genitourinary fistulae were admitted and managed. The mean age of patients with urinary fistulae was 31.5±7.5 years, parity was 4.2±2.8, and duration of labour was 38.4±6.5 hours. The duration of fistulae ranged from 1 day to 25 years. Obstructed labour 246 (88.4%) was the most common cause of urinary fistulae, followed by gynaecological surgeries mainly hysterectomies 26 (9.35%). The most common type of urinary fistula was vesico-vaginal fistula (VVF) 250 (89.9%). A total of 268 underwent surgery. Almost all 261 (97.3%) urinary fistulae were repaired transvaginally except patients with ureterovaginal and vesico-uterine fistulae. The most common surgical procedure used was layered closure. Martius graft was used in 3 (1.1%) patients, who required creation of new urethra. The success rate following first, second and third attempt was 85%, 91% and 96% respectively. Conclusion: Urogenital fistulae are rarity in developed world, but are frequently encountered problem in developing countries like Pakistan, often resulting from prolonged obstructed labour due to poor obstetric care. Utilising basic principles of surgery, all types of urinary fistulae can be repaired. Keywords: uro-genital fistulae, VVF, aetiology, surgery